Introducing Numbers to Early Childhood Children by Using Number Cards in PAUD Negeri 2 Banda Aceh - Ahmad, Anizar; Yuhasriati, Yuhasriati; Nurchasanah, Sitti (Indonesian Journal of Early Childhood Education Studies, 2017)
Number cards is one of simple media that can be used to help introduce early childhood children to numbers and numeral symbols. Formulation of the problem of this research are, 1) How do we introduce numbers to children by using number cards in PAUD Negeri 2 Banda Aceh? 2) How is the children’s responses to the learning method of numbers introduction by the use of number cards in PAUD Negeri 2 Banda Aceh? The purposes of this research are: 1) to introduce numbers to children by the use of number cards in PAUD Negeri 2 Banda Aceh; 2) to understand childrens’s responses to the learning method of numbers introduction by the use of number cards in PAUD Negeri 2 Banda Aceh. The research is Classrom Action Research (PTK). The research subjects are 25 children of Group A in PAUD Negeri 2 Banda Aceh. The action is combined with stories, games, and contests. Data collection is done by observation and work method. Data analysis technique is using descriptive analysis. Conclusions of this research are; 1) Introducing numbers to early childhood children by using number cards can be done with stories, games, and contests. 2) Students’ responses to the learning method of numbers introduction by the use of picture cards that is done with stories, games, and contests are generally positive. 3) The results of work method about numbers introduction by the use of number cards that is done with stories, games, and contests are generally good at the developmental aspect, that children can compile, sort, and mention numeral symbol corresponding to amount of items in the picture that are shown.